European Jewry and the First Crusade - Chazan, Robert (Berkeley : University of California Press, 1996)
One of the unanticipated results of the First Crusade in 1095 was a series of violent assaults on major Jewish communities in the Rhineland. Robert Chazan offers the first detailed analysis of these events, illuminating the attitudes that triggered the assaults as well as the beliefs that informed Jewish reactions to them.
The background -- The sources and their reliability -- The violence of 1096 -- The patterns of response -- Subsequent Jewish reactions -- The church, the Jews, and the later Crusades -- Glances backward and forward.
First paperback printing, 1996.
Includes bibliographical references (pages 357-367) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Jews -- Germany -- History -- 1096-1147.; Jews -- Persecutions -- Germany; Crusades -- First, 1096-1099 -- Jews -- Germany; Germany -- Ethnic relations; Juifs -- Allemagne -- Histoire -- 1096-1147.; Juifs -- Persécutions -- Allemagne; Croisades -- 1re croisade, 1096-1099 -- Juifs -- Allemagne; HISTORY; RELIGION / Judaism / General; Crusades; Ethnic relations; Jews; Jews -- Persecutions; Germany; 1096-1147; History